Preparation and release characteristics study on the novel minocycline hydrochloride sustained-release capsule (Bangladesh Journal of Pharmacology, 2016)
In present study, a novel minocycline hydrochloride sustained-release capsule was prepared with the new extrusion-spheronization method. The in vitro release studies were performed using marketed sample as a reference and data were analyzed in terms of cumulative release amounts as a function of time. Results demonstrated that the developed analysis method was reliable and convenient for the quantification and dissolution study of minocycline hydrochloride. The release characteristics of different batches of preparations were quite similar with each other, similarity factors f2  of 12 batches were all within 50-100, and our developed sample was similar to reference preparation in release characteristics in vitro. The developed sustained-release preparation may be a promising alternative dosage form for treatment of related diseases.